Infanticide Cases at a Top Referral Hospital in West Java, Indonesia: Prevalence and Causes from 2019 to 2023 - Lumbantoruan, Luna Oktavia; Novita, Nita; Yosiati, Naomi (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Infanticide refers to the intentional killing of a newborn by the biological mother shortly after birth, which can be proven through internal and external forensic examinations. This study aimed to determine the prevalence and causes of suspected infanticide cases at a top referral hospital in West Java, Indonesia.Methods: A descriptive study was conducted using total sampling of all Visum et Repertum reports from 2019 to 2023 at the Department of Forensic and Legal Medicine, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. A total of 1,531 forensic cases were reviewed. Data on characteristics and findings from internal and external examinations were collected and analyzed.Results: Of 1,531 cases, the most common classification was death on arrival (n=480), whereas suspected infanticide ranked fourth (n=50). However, only 16 cases met the established forensic criteria for infanticide. The leading cause of deaths was head injury due to blunt force trauma (37.5%), followed by undetermined causes (25%), hypothermia (12.5%), asphyxia (12.5%), drowning (6.25%), and neglect (6.25%).Conclusions: The prevalence of confirmed infanticide is 1.05%, with blunt head trauma being the most common cause of death. These findings highlight the urgent need for government intervention to evaluate population and family development programs, including reproductive health education, readiness for marriage, and parenting responsibilities in school curricula. Promoting comprehensive education and responsible parenting may reduce the incidence of infanticide and support healthier family environments for future generations.